2010
DOI: 10.1186/1743-422x-7-208
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of the cell-adapted PanAsia strain of foot-and-mouth disease virus O/Fujian/CHA/5/99 isolated from swine

Abstract: BackgroundAccording to Office International Des Epizooties (OIE) Bulletin, the PanAsia strain of Foot-and-Mouth Disease Virus (FMDV) was invaded into the People's Republic of China in May 1999. It was confirmed that the outbreaks occurred in Tibet, Hainan and Fujian provinces. In total, 1280 susceptible animals (68 cattle, 1212 swine) were destroyed for the epidemic control.To investigate the distinct biological properties, we performed plaque assay, estimated the pathogenicity in suckling mice and determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…BHK-21, WT-CHO and pgsD-677 cell monolayers in 6-well plates were inoculated with the serial ten-fold dilutions of all the selected PanAsia-1 strains and rescued viruses, following the previously described procedures [46]. The values of plaque titrations of each virus were calculated as described previously [24].…”
Section: Methodsmentioning
confidence: 99%
“…BHK-21, WT-CHO and pgsD-677 cell monolayers in 6-well plates were inoculated with the serial ten-fold dilutions of all the selected PanAsia-1 strains and rescued viruses, following the previously described procedures [46]. The values of plaque titrations of each virus were calculated as described previously [24].…”
Section: Methodsmentioning
confidence: 99%
“…Residue 142 lies within the GH loop close to the RGD motif and modulates the spatial orientation of the GH loop depending on the amino acid at this position [63]. Substitutions at residue 142 have been reported for all Eurasian FMDV serotypes [51,53,55,57,63]. These substitutions are highly variable and differ depending on the cell line in which the virus was cultured [51,55,63].…”
Section: Virus Protein Vp1mentioning
confidence: 99%
“…Furthermore, changes in this part of VP2 are often described to occur in combination with substitutions in VP1 [58,63] during passaging in BHK cells [15,71]. Another well-described phenomenon for serotype A and O are amino acid exchanges at positions 133, 134, and 136 [13,15,51,54,57,72]. This region lies within the αB helix of VP2 (residues 133-138) and is part of the depression that is used for HS binding [48].…”
Section: Virus Protein Vp2mentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue culture adapted virus, which utilizes heparin sulfate (HS) receptor, was shown to be relatively avirulent in cattle compared with wild-type virus that utilizes integrin receptors (28,36). It was also found that the plaques produced by the HS-binding virus on BHK-21 cells are smaller than the integrin-binding virus (2). The role of 3A protein in viral virulence has also been demonstrated.…”
Section: Discussionmentioning
confidence: 93%